Profitabilitas terhadap Financial Distress Dimediasi Corporate Social Responsibility - Supami Wahyu Setiyowati; Mardiana Mardiana (Fakultas Ekonomi, UIN Maliki Malang, 2022)
Financial distress is the state of a company’s financial constraints. The purpose of this study was to determine the profitability of financial distress mediated by the disclosure of CSR. The population of this study are manufacturing BEI companies in 2016-2020. The sampling technique used is proportional sampling, which amounted to 55. The data analysis technique used Smart PLS. The results of this study indicate that profitability has a negative effect on financial distress. Profitability affects the CSR. CSR has a negative effect on financial distress. Profitability has an effect on financial distress mediated by CSR. This research the company must maintain the factors that can reduce financial distress.